2016
DOI: 10.1002/art.39753
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Biopsy Findings in Combination With Myositis‐Specific Autoantibodies Aid Prediction of Outcomes in Juvenile Dermatomyositis

Abstract: ObjectiveJuvenile dermatomyositis (DM) is a rare and severe autoimmune condition characterized by rash and proximal muscle weakness. While some patients respond to standard treatment, others do not. This study was carried out to investigate whether histopathologic findings and myositis‐specific autoantibodies (MSAs) have prognostic significance in juvenile DM.MethodsMuscle biopsy samples (n = 101) from patients in the UK Juvenile Dermatomyositis Cohort and Biomarker Study were stained, analyzed, and scored for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 26 publications
4
48
2
1
Order By: Relevance
“…It is not known whether particular antibodies predate the specific features with which they are associated: they could be useful as prognostic biomarkers. In support of this, a recent study demonstrated that the MSA status in combination with the muscle biopsy score can be a significant prognostic tool [24].…”
Section: Cd4mentioning
confidence: 56%
“…It is not known whether particular antibodies predate the specific features with which they are associated: they could be useful as prognostic biomarkers. In support of this, a recent study demonstrated that the MSA status in combination with the muscle biopsy score can be a significant prognostic tool [24].…”
Section: Cd4mentioning
confidence: 56%
“…In contrast, juvenile IIMs are rare and few sero‐pathological correlations have been reported. Our group has previously shown differences in histopathological severity between the MDA5 and Mi2 serological groups and described distinctive features of the paediatric patients positive for MDA5 . SRP and HMGCR serological groups appear to be associated with necrotizing myopathies in children as they are in adults .…”
Section: Introductionmentioning
confidence: 69%
“…As we have previously shown, muscle biopsy scores for patients with MDA5‐associated myopathies cluster in the mild range, Mi2‐associated cases cluster in the severe range, and TIF1γ‐ and NXP2‐associated cases vary across a wide range, Figure . To further analyse these findings, we conducted PCA using all 101 sets of biopsy score data.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations